2000
DOI: 10.1103/physrevb.61.10807
|View full text |Cite
|
Sign up to set email alerts
|

Localized triplet excitations and the effect of photo-oxidation in ladder-type poly(p-phenylene) and oligo(p-phenylene)

Abstract: The photophysics of methyl-bridged poly͑para-phenylene͒-type ladder polymer ͑m-LPPP͒ and oligomer films and solutions is described and discussed. The spin sensitive properties, such as the formation and properties of polaron pairs and triplet excitons ͑TE's͒ were studied using X-band photoluminescence ͑PL͒ detected magnetic resonance ͑PLDMR͒. The PLDMR results and quantum chemical calculations show unambiguously that the TE wave-function extent is much smaller than that of the singlet exciton ͑SE͒. The weaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 42 publications
3
51
1
Order By: Relevance
“…For m-LPPP, TSC measurements have revealed mostly shallow traps with a density of at least 2ϫ10 16 cm Ϫ3 for polarons with an average activation energy of 60 meV, 26 in agreement with the energetic disorder parameter ϭ50 meV ͑Ref. 37͒ found from time-of-flight measurements.…”
Section: Bimolecular Decaysupporting
confidence: 63%
See 2 more Smart Citations
“…For m-LPPP, TSC measurements have revealed mostly shallow traps with a density of at least 2ϫ10 16 cm Ϫ3 for polarons with an average activation energy of 60 meV, 26 in agreement with the energetic disorder parameter ϭ50 meV ͑Ref. 37͒ found from time-of-flight measurements.…”
Section: Bimolecular Decaysupporting
confidence: 63%
“…This difference in ⌬H 1/2 is attributed to the decreased polaron pair separation ͑and hence increasing dipolar broadening͒ in the oligomer, in agreement with results found from a comparison of these resonances in frozen m-LPPP solutions and m-LPPP films. 25,26 There it was found that ⌬H 1/2 is drastically reduced in solution due to the increased chain separation. In the polymer and oligomer of this work the situation is similar due to the much smaller side groups of the latter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is assumed that the polymer chain is divided into segments bound by conformational or chemical defects, one normally assumes that the singlet exciton occupies most of the segment, a phenomenon known as the effective conjugation length ͑typically 25-30 repeat units͒. 41,42 Conversely, the triplet exciton is understood to only occupy a segment of a few phenyl rings; [43][44][45] thus, if the reasonable assumption that each chain segment can only hold one excitation ͑either singlet or triplet͒, then the mean distance from the singlet to the neighboring triplet exciton is large and the necessary overlap of the states required for intrachain STA by Dexter transfer would not be possible. Additionally, given this constraint, the singlet would be outside the Förster radius of the triplet and the energy transfer could not proceed by a Forster mechanism either.…”
Section: Singlet-triplet Annihilationmentioning
confidence: 99%
“…The availability of soluble PPV oligomers makes it possible to study their intrinsic molecular properties, and extrapolate to the behaviour of the related polymer [5,7,13,14]. Moreover, the study of these compounds in dilute solutions allows their characterization in the absence of significant effects due to interchain interactions and under conditions where the time between collisions of two oligomers is longer than the lifetimes of the excited states under investigation.…”
Section: Introductionmentioning
confidence: 99%